2022
DOI: 10.3390/ijms232315197
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decline in Nrf2/ARE Signaling Is Associated with the Mitochondrial DNA Damage and Cognitive Impairments

Abstract: In this research, we compared the cognitive parameters of 2-, 7-, and 15-month-old mice, changes in mitochondrial DNA (mtDNA) integrity and expression of genes involved in the nuclear erythroid 2-related factor 2/antioxidant response element (Nrf2/ARE) signaling pathway. We showed an age-related decrease in the Nfe2l2 expression in the cerebral cortex, not in the hippocampus. At the same time, we find an increase in the mtDNA copy number in the cerebral cortex, despite the lack of an increase in gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
3
7
0
Order By: Relevance
“…This was accompanied by the decreased expression of three known targets of the NRF2 pathway, NQO1, GCLC, and GCLM. Similary, an age-dependent decrease in the mRNA levels of NRF2 was shown in the cortex of wild-type mice [90]. The high KEAP1 and low GCLC, HO-1, NRF2, and NQO1 gene and protein expression levels in the H 2 O 2 group in our study are similar to those reported by Kanninen et al [89] and Gureev et al [90] in aged mice.…”
Section: Discussionsupporting
confidence: 91%
“…This was accompanied by the decreased expression of three known targets of the NRF2 pathway, NQO1, GCLC, and GCLM. Similary, an age-dependent decrease in the mRNA levels of NRF2 was shown in the cortex of wild-type mice [90]. The high KEAP1 and low GCLC, HO-1, NRF2, and NQO1 gene and protein expression levels in the H 2 O 2 group in our study are similar to those reported by Kanninen et al [89] and Gureev et al [90] in aged mice.…”
Section: Discussionsupporting
confidence: 91%
“…It is interesting to note in this respect that BRCA1 and ATM have both been shown to be crucially involved in GIT2-associated DDR processes [22]. As we have previously discussed, there is a near-inevitable link in aging between metabolic dysfunction and DNA damage [6,71,[137][138][139]. With this knowledge, we assessed whether the DDR-based stress response component of the GPR19 molecular signature was also linked to energy metabolic processes.…”
Section: Discussionmentioning
confidence: 94%
“…Nrf2 translocates to the nucleus under oxidative stress, promoting antioxidant gene expression, such as GCS, HO1, and SOD1 [ 86 , 87 ]. There is a general consensus that Nrf2 signaling is reduced during aging [ 88 , 89 ]; however, several reports show controversial results of unchanged or increased Nrf2 in the hippocampus of aged male animals [ 90 ]. A study on the cerebellum of 21m male mice showed increased transcript and protein levels of Nrf2 with an increase in its antioxidant target genes [ 91 ].…”
Section: Discussionmentioning
confidence: 99%